Komunikacja wewnętrzna a zaangażowanie pracowników - Karaszewski, Robert; Jóźwik, Barbara; Skrzypczyńska, Kamila (Communication and Employees' Engagement, 2008)
Communication is mutual transferring of information, skills, concepts, ideas, feelings etc. by symbols created by the combination of words, sounds, pictures, and touch. It is a specific social process which occurs in specific context determined by the number and character of its participants. Communication is aimed, willful and has very dynamic character. It is permanent, complex and irreversible process. Communication in an organization is one of the areas of so-called "soft management" and is one of the bases of good climate at work. It is also one of the levels of R. Nellson's hierarchy of wants. Many different instruments may be used in this process, depending on its character, purpose and situation. As one of the areas of "soft management" it is strictly related to some lack of predictability and various traps. There is no doubt that the quality of communication in an organization has the influence on employees' motivation and their satisfaction, engagement, and efficiency. Engagement, as each attitude, has a few dimensions. It can be said about engagement on the level of knowledge, emotions and behaviour, and each of those dimensions can be stimulated in a different way, by various incentives. It is one of eight fundamental principles of excellence which create EFQM model, in which excellence means maximization of employees' involvement through their development and engagement. This attitude is one of the elements of the economic model of behaviour for organizations, known as the microeconomic Gallup path model, and is correlated with five new management rules indicated by J. Fleming and J. Asplund in their HumanSigma concept. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 365-377